Survival and multi-omics analysis of immunotherapy-based conversion treatment for initially unresectable gastric cancer - Li, Song; Xu, Qian; Yu, Wenbin; Liu, Zimin; Cui, Xiaohan; Wei, Meng; Shi, Duanbo; Zhao, Wen; Song, Xinyu; Zhang, Di; Nan, Zhaodi; Chu, Jiahui; et al. (Frontiers in Immunology, 2026)
BackgroundImmune checkpoint inhibitors (ICIs) have demonstrated efficacy in the treatment of resectable and advanced gastric cancer. However, their effectiveness in initially unresectable gastric cancer remains unclear. This study aims to evaluate the efficacy and elucidate the molecular mechanisms of conversion therapy utilizing ICIs in patients with initially unresectable gastric cancer.MethodsThis retrospective cohort study included patients with initially unresectable locally advanced or oligometastatic gastric cancer treated with ICIs-based therapy for conversion purposes. The primary endpoints were rates of complete pathological response (pCR), major pathological response (MPR), and R0 resection. Secondary endpoints included overall survival (OS), disease-free survival (DFS), event-free survival (EFS) and safety. A multi-omics analysis was performed on the tumor samples.ResultsA total of 73 patients were analyzed, with 75.3% at stage cIV. The median EFS and OS were 26.1 and 41.3 months, respectively. 82.2% of the patients underwent radical surgery and achieved a median EFS of 30.9 months. The pCR and MPR rates were 24.7% and 37.0%, respectively. R0 resection was associated with superior survival, and MPR further enhanced efficacy. The incidence of adverse effects and postoperative complications were within acceptable limits. KMT2D mutations were associated with improved outcomes and enhanced immune responses, whereas tumor cytochrome P450 was linked to resistance.ConclusionICIs-based conversion therapy demonstrates promising survival benefits and manageable safety profiles for patients with unresectable locally advanced or oligometastatic gastric cancer, and provides real-world evidence for a potential treatment strategy. Additionally, multi-omics findings have revealed drug resistance mechanisms and potential biomarkers of efficacy.